The impact of the Covid-19 pandemic on endodontic care and procedures: literature review (Research, Society and Development, 2022)
The current outbreak of Coronavirus strain 2019 (Covid-19) constitutes a public health emergency of global concern due to its high virulence and power of dissemination in the population, which entails high demand for highly complex hospital care. For dental care there is an increased risk, since SARS-CoV-2 ("Severe Acute Respiratory Syndrome Coronavirus 2") can be detected in saliva in several ways, such as in the lower and upper respiratory tract when it comes into direct contact with the oral cavity, contaminating it. Given the need for knowledge and adaptation regarding the dental care related to the pandemic period, the interest in addressing the relationship of Covid-19 regarding the care and procedures related to endodontics arose. The aim is to describe the specialty the to present biosafety guidelines related to the care and conduct used during the pandemic moment. The present study will follow the model of literature review or bibliography as described in other literature, of narrative type, where it will be assigned to this research, the articles, projects, information considered relevant for its construction. Many are the particularities regarding dental care in the context of the pandemic and, because of this, care protocols had to be modified and guidelines applied aiming at the mitigation and protection of the team, the professional and the patients, being constantly updated and incorporated into the daily routine, as presented by ANVISA and the Ministry of Health. The adequacy and continuity of the application of protocols created during this period should continue to be used and professionals should seek to keep themselves updated, since in constantly changing, as our measures of protection, prevention and control require optimization and improvement, seeking to play an important role in the spread of contamination of Covid-19.